STUDI BIBLIOMETRIK PADA JURNAL STANDARDISASI PASCA TERAKREDITASI (2011-2015) - Abdul Rahman Saleh; Erni Sumarni (Perpustakaan Nasional RI, 2016)
The objective of this study is identifying articles published in the Journal of Standardization during 2011 to 2015 after the accreditation. The identification was done to figure out the patterns of the authorship, collaborative level, literature characteristics, anovelty of the citations, and obsolescence of the literature. Data was taken from all articles of the journal starting from volume 13 of 2011 to volume 17 of 2015. During this period, the Journal of Standardization published 120 articles written by 187 authors. Results showed that the most productive author were Danar Agus Susanto and Ellia Kristiningrum who wrote 8 articles each. Collaborative level of authorship in the journal was 0.658 (65.8%). The most authors in one article was found to be 6. Book was the most used collection with 42.3% of usability under the age of 5 years. The obsolescence level of the reference used in the journal was 6 years. The usability of the articles retrieved from Google Scholars was found to be low with 6 articles out of 120 articles published in the last 5 years.